Use of Gibberellic Acid Treatments to Improve Health and Yield of HLB-Affected Sweet Orange Trees (Part 1 of 2) - T. Vashisth; A. Singerman (EDIS, 2023)
This publication discusses gibberellic acid use in citrus. Written by T. Vashisth and A. Singerman, and published by the UF/IFAS Horticultural Sciences Department, February 2023.